Should Defined Contribution Plans Include Private Equity Investments?. Issue 4 (2nd October 2022) - Brown, Gregory W.; Crouch,, Keith J.; Ghent, Andra; Harris, Robert S.; Hochberg, Yael V.; Jenkinson, Tim; Kaplan, Steven N.; Maxwell, Richard; Robinson, David T.
Abstract: This paper evaluates the pros and cons of including private equity fund investments in defined contribution plans. Potential benefits include higher returns and improved diversification as well as a relatively safe method for accessing investments previously only available to institutions and the very wealthy. Despite these enticing benefits, they need to be weighed against potential challenges and costs that may arise from creating this broader access to private funds. The complicated structure and uncertainty around the mechanism to provide required liquidity backstops may bring increased fees or even disrupt the private fund model.